Paddy machine / Lister Larry Simon ... [et al.] - Simon, Lister Larry; Mohd. Shariff, Ikmal Hussein; Hussin, Abdul Wahid; Saalah, Herman; Mohd. Sobri, Mohd Izwan (2005)
The entire project begins with analyzing problems from the environment. After that, the group will collect data. From the data, they can make hypothesis and then experiment. If the experiment success, a new product will be produced to solve the existing problem. To ran the project smoothly, they will be guided with one supervisor and raw material will be provide.